RELATIONSHIP OF FORMER HISTORY OF DIARRHEA AND SANITATION WITH THE PREVALENCE OF STUNTING AMONG CHILDREN AGED 1–5 YEARS IN SIDOTOPO WETAN, SURABAYA - Naisya Azalia Samsuddin; Emyr Reisha Isaura; Sri Sumarmi (Universitas Airlangga, 2021)
Stunting deﬁnes as an abnormal linear growth of children less than -2 standard deviations (SD) of the height measurements according to age. According to WHO (2013), the quality and quantity of nutrient intake and the presence of infectious diseases are directly associated with stunting, while hygiene and sanitation are indirectly associated with stunting. This study aimed to determine whether there is a relationship between disease history and sanitation with the incidence of stunting in children aged 1-5 years in the working area of Sidotopo Wetan Health Center (Puskesmas), Surabaya City. This cross- sectional study was used secondary data from the survey of Puskesmas Sidotopo Wetan children under ﬁve - supervising program 2020 which included 166 children aged ≤ 5 years. The dependent variable was stunting, and the independent variables are the history of diarrheal disease and sanitation facilities. The results found that 77 children under ﬁve were stunting (46.40%), history of frequent diarrhea was 19.26%, history of the last one month of having diarrhea was 20.47%, permanent healthy toilet ownership 89%, and qualiﬁed trash bin were 46.97%. The results of the chi-square statistical test on the research variables further showed a positive relationship with a history of frequent diarrhea (p = 0.023) and diarrhea during the past month (p = <0.001) with the incidence of stunting. There was also a negative relationship between the toilet (p = <0.001) and trash bin ownership with the incidence of stunting (p = 0.023). Thus, this study concludes that the history of diarrhea and environmental sanitation factors of toilet and trash bin ownership have a relationship with the incidence of stunting in children under ﬁve years old. The stunting prevention program shall more consider the awareness of the parents and their kids about nutrient intake, practice of hygiene and sanitation in the house.